ChemInform Abstract: Asymmetric Aldol Reaction Organocatalyzed by Bifunctional N‐Prolyl Sulfinamides under Solvent‐Free Conditions. Issue 5 (February 2015) - Wan, Wen; Gao, Wei; Ma, Guobin; Ma, Lei; Wang, Fan; Wang, Jing; Jiang, Haizhen; Zhu, Shizheng; Hao, Jian
Abstract All aldehydes (II) form the corresponding products (III) with high to excellent diastereoselectivity in favor for the anti‐isomer, whereas furan‐2‐carbaldehyde is transformed to the corresponding aldol product with only moderate diastereoselectivity.